2009
DOI: 10.1111/j.1745-6584.2008.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Potential Recharge in Mantled Sinkholes Using ERT

Abstract: Potential recharge through thick soils in mantled sinkholes was quantified using differential electrical resistivity tomography (ERT). Conversion of time series two-dimensional (2D) ERT profiles into 2D volumetric water content profiles using a numerically optimized form of Archie's law allowed us to monitor temporal changes in water content in soil profiles up to 9 m in depth. Combining Penman-Monteith daily potential evapotranspiration (PET) and daily precipitation data with potential recharge calculations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
(50 reference statements)
1
17
0
Order By: Relevance
“…For shallower water tables, a linear relationship between depth to the water table and water-level response time is evident in granular porosity aquifers [58]. Typically, connected sinkholes add large volumes of water to the aquifer in a relatively short time, while conduit systems in the aquifer may rapidly transport and remove it leading to short residence time [24]. This is evident in recent water level responses to an extreme rain event in the Robinson lens, where 109 mm of rainfall was received on 14 February 2014.…”
Section: Aquifer Water Level Response To Extreme Rainfall Event and Amentioning
confidence: 99%
See 2 more Smart Citations
“…For shallower water tables, a linear relationship between depth to the water table and water-level response time is evident in granular porosity aquifers [58]. Typically, connected sinkholes add large volumes of water to the aquifer in a relatively short time, while conduit systems in the aquifer may rapidly transport and remove it leading to short residence time [24]. This is evident in recent water level responses to an extreme rain event in the Robinson lens, where 109 mm of rainfall was received on 14 February 2014.…”
Section: Aquifer Water Level Response To Extreme Rainfall Event and Amentioning
confidence: 99%
“…Sinkholes connected to the watertable bypass the soil zone, directly recharging the aquifer as point recharge. Unconnected sinkholes add runoff deeper into the unsaturated zone, which can then rapidly drain into the watertable via macropores and slow infiltration through the soil profile between the sinkhole bottom and watertable plane [14,24]. Karstic features supply a significant amount of recharge to many carbonate aquifers in temperate and humid regions throughout the world [16], yet the applicability of the assumptions used in recharge estimation methods has not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, an air-filled void would generate a high-resistivity anomaly, but this would not constitute a sinkhole, strictly speaking. ERT sections acquired in a karst area outside an urbanized environment should clearly display the types of anomalies routinely encountered in sinkholes (Dobecki and Upchurch, 2006;Schwartz and Schreiber, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Hydrogeologic and environmental factors such as the water content, porosity, salinity, clay content, pore geometry, and pore-fluid temperature control the electrical resistivity of a medium (Everett, 2013). ERI surveys can be used to delineate 15 groundwater discharge areas (Nyquist et al, 2008), recharge pathways through mantled sinkholes (Schwartz and Schreiber, 2009), and riverbed sediment architecture (Crook et al, 2008). Daily et al (1992) showed that ERI can effectively map changes in water content within the vadose zone by analyzing the temporal changes in electrical resistivity as a result of an infiltration event.…”
mentioning
confidence: 99%